A STUDY OF SYMPATHY EXPRESSIONS IN ENGLISH AND VIETNAMESE - Hoàng Lưu Bảo (Trường Đại học Ngoại ngữ, 2025)
This study attempts to investigate the syntactic and pragmatic features of sympathy expressions (SEs) in English and Vietnamese. It focuses on the ways people to express their sympathy in both English and Vietnamese language. To discuss the issues thoroughly we use data from English and Vietnamese novels and short stories. The most inportant and significant aspect of the study is the similarities and differences between people from speaking countries and the Vietnamese in ways of expressing sympathy. Some typical strategies used in performing SEs in English and Vietnamese were presented in the light of the politeness theory by Brown and Levinson (1987). On the basis of findings, some implications are put forward for the teaching and learning English for the Vietnamese learners concerning speech acts in general and SEs in particular.